ZAKAT DALAM PERSPEKTIF FIKIH STATIS DAN DINAMIS - Syahriyah, Eri; Yusuf, Enjang Burhanudin (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study examines the understanding and practice of zakat through the lenses of static and dynamic fiqh. The aim is to preserve the essence of zakat as a mandatory act of worship rooted in Islamic law, while adapting its implementation methods to remain relevant and impactful in today's socio-economic context. The research uses a descriptive qualitative approach through library research, analyzing both classical and contemporary literature on zakat law in a modern framework. Findings indicate that static fiqh plays a crucial role in safeguarding the purity of zakat regulations based on scriptural texts and established schools of thought. Meanwhile, dynamic fiqh allows for adaptation to modern forms of wealth, innovative distribution methods, and the integration of technology. These approaches are not contradictory but complementary, ensuring both the preservation and actualization of zakat in the modern era. This study contributes to contemporary zakat jurisprudence by supporting the development of contextual, productive, and digital zakat models. It also serves as a reference for zakat institutions to remain Sharia-compliant while being responsive to social and economic changes. As a theoretical, literature-based study, it does not include empirical data. Therefore, further research using quantitative or field-based qualitative methods is recommended to strengthen these findings.